Screening and validation of genome-edited animals. (February 2022) - Bunton-Stasyshyn, Rosie K; Codner, Gemma F; Teboul, Lydia
The emergence of an array of genome-editing tools in recent years has facilitated the introduction of genetic modifications directly into the embryo, increasing the ease, efficiency and catalogue of alleles accessible to researchers across a range of species. Bypassing the requirement for a selection cassette and resulting in a broad range of outcomes besides the desired allele, genome editing has altered the allele validation process both temporally and technically. Whereas traditional gene targeting relies upon selection and allows allele validation at the embryonic stem cell modification stage, screening for the presence of the intended allele now occurs in the (frequently mosaic) founder animals. Final confirmation of the edited allele can only take place at the subsequent G1 generation and the validation strategy must differentiate the desired allele from a range of unintended outcomes. Here we present some of the challenges posed by gene editing, strategies for validation and considerations for animal colony management.